Managing Density Stress to Close the Maize Yield Gap - Winans, Eric T.; Beyrer, Tryston A.; Below, Frederick E. (Frontiers in Plant Science, 2021)
Continued yield increases of maize (Zea mays L.) will require higher planting populations, and enhancement of other agronomic inputs could alleviate density-induced stress. Row spacing, plant population, P-S-Zn fertility, K-B fertility, N fertility, and foliar protection were evaluated for their individual and cumulative impacts on the productivity of maize in a maize-soybean [Glycine max (L.) Merr.] rotation. An incomplete factorial design with these agronomic factors in both 0.76 and 0.51 m row widths was implemented for thirteen trials in Illinois, USA from 2014-2018. Agronomic treatments were compared to two controls: enhanced and standard, comprising all factors applied at the enhanced or standard level, respectively. The 0.51 m enhanced management control yielded 3.3 Mg ha-1 (1.8-4.6 Mg ha-1 across environments) more grain (25%) than the 0.76 m standard management control, demonstrating the apparent yield gap between traditional farm practices and attainable yield through enhanced agronomic management. Narrow rows and the combination of P-S-Zn and K-B fertility were the factors that provided the most significant yield increases compared to the standard control. Increasing plant population from 79,000 to 109,000 plants ha-1 reduced the yield gap when all other inputs were applied at the enhanced level. However, increasing plant populations alone did not increase yield when no other factors were enhanced. Factors such as narrow rows and availability of plant nutrition become more critical with increasing plant population when density-induced stress is more significant. Changes in yield were dependent upon changes in kernel number. Kernel weight was heaviest when all management factors were applied at the enhanced level while only planting 79,000 plants ha-1. Conversely, kernel weight was lightest when increasing population to 109,000 plants ha-1 while all other factors were applied at the standard level. The yield contribution of each factor was generally greater when applied in combination with all other enhanced factors than when added individually to the standard input system. Additionally, the full value of high-input agronomic management is only realized when matched with greater plant density.